Elemental Sulfur as a Catalyst Precursor for Gas-Liquid Heterogeneous Chlorination of Acetic Acid: Kinetics and Optimization for Enhanced Monochloroacetic Acid Selectivity and Productivity - Kwang Il Wi; Ri Myong Kim; Tae Hun Ryo; Song Chol Ri; Nam Chun Kim; Hak Chol Han; Un Chol Han; Hae Song Choe; Kwang Won Ri (Journal of Chemical Engineering Research Progress, 2026)
Monochloroacetic acid (MCA) is a pivotal intermediate in agrochemicals and pharmaceuticals, but its industrial synthesis via acetic acid chlorination faces challenges related to selectivity and reaction time．According to literature reports, in conventional processes, MCA selectivity is typically 70-85% at 80-90% conversion, and reaction time is 25-35 hours. This study investigates the kinetics of gas-liquid heterogeneous acetic acid chlorination using elemental sulfur as a catalyst precursor to establish a scientific basis for process optimization. A consecutive-parallel reaction mechanism was proposed incorporating acetic acid consumption, acetyl chloride conversion, MCA formation, and dichloroacetic acid (DCA) formation. Kinetic parameters were determined at 353, 363, 373, and 383 K in a steel bubble column reactor with fixed initial sulfur concentration (1.92 mol.L-1) and Cl₂ space velocity (4.028 L.L⁻¹.h⁻¹). The activation energy for DCA formation (87.55 kJ.mol⁻¹) was substantially higher than that for MCA accumulation (52.40 kJ.mol⁻¹). Relative rate analysis revealed that k₃/k₄ decreases continuously from 1.83 at 353 K to 0.76 at 383 K, confirming that lower temperatures favor MCA selectivity. When the low-temperature (353K) operation strategy proposed in this study is applied, selectivity can be improved to approximately 88-92% (a 15-20 percentage point improvement compared to conventional processes). By applying the optimal temperature-time profile, the reaction time can be reduced to approximately 20-22 hours (a 25-35% reduction compared to conventional processes). The proposed kinetic model showed excellent agreement with experimental data (R² > 0.98). Based on the kinetic analysis, three optimization strategies were derived: maintaining high acetic acid concentration, dynamic adjustment of Cl₂ feed rate, and implementation of a decreasing temperature-time profile. This work provides a scientific basis for optimizing industrial MCA synthesis using low-cost sulfur as a catalyst precursor. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).